Pengembangan dan Validasi Emosional Pembelajaran dalam Survei Lingkungan Kelas Daring - Erwin Sulaeman (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2021)
The purpose of this research is to produce an Indonesian version of the emotional learning online classroom environment survey instrument with a response category scale. Instruments from a modified Learning Environment Research Questionnaire on Classroom Emotional Climate. This research is a survey on 1494 responses of 7th grade and 8th grade junior high school students in four regions of DKI Jakarta Province. The sample was selected by simple random sampling and based on the considerations of schools implementing the 2013 curriculum. The modified instrument consisted of 43 items to be tested in obtaining validity based on the estimated difficulty of the items and the psychometric criteria with Rasch modeling. The results of this study indicate that the Andrich threshold test fulfills the monotonic nature and unconsciously the students' responses form an emotional culture that prioritizes self-awareness in online learning. Therefore, for the psychological scale compilers are expected to compile statement items that are easy to understand and build good interactions with respondent, so that the respondent feels not intervened. This trend may even increase when sensitive issues of concern statement appear in the instrument items. Characteristics of psychologically motivated instruments, written in the statement items intervene on sensitive issues in the learning environment.